IMPLEMENTASI MANAJEMEN LAYANAN BIMBINGAN KONSELING DI MADRASAH ALIYAH IBNU ABBAS AS SALAFY JAWA TENGAH - Lilik Pujianto; Cipto Handoko; Sunarto (UNISAN JURNAL, 2022)
The purpose of this study was to determine the counseling service program in MA Ibnu Abbas As Salafy Central Java in terms of management functions, namely planning, implementation and evaluation. The research was conducted at the MA Ibn Abbas As Salafy, Central Java. This study uses a qualitative method with a descriptive approach, data collection through interviews, documentation and observation, the validity of the data used is triangulation. The data sources in this study were the Principal, BK teachers, homeroom teachers, and students. Based on the results of the study, it can be concluded that 1) The planning of the guidance and counseling program at the MA Ibnu Abbas As Salafy Central Java is good, covering 3 stages; a) Preparation of a program of activities consisting of setting goals, formulating program forms such as annual, monthly and daily programs, b) Preparation of personnel, carried out so that the implementation of the BK program can run well, so that there is no overlapping of responsibilities and duties. c) Provision of required facilities include; Guidance room and room equipment, consisting of: data storage area and whiteboard and bulletin board. 2) Implementation of Counseling Guidance at MA Ibnu Abbas As Salafy Central Java is not good, there are some guidance and services that have not been maximally implemented, this is caused by 3 things, namely a) Non-linear educational background of BK teachers so that the service is not optimal, b ) Lack of socialization of the BK program, and c) Limited time. 3) The evaluation carried out has not been good, because it has not been able to accurately measure the effectiveness of the BK program implemented, and the absence of a clear evaluation design is the main factor in the difficulty of measuring the success of the program. Keywords: Management Implementation, Education Quality, Madarasah Ibtidaiyah